Computer security factors effects towards online usage of internet banking system - Al-Shawabkeh, Mahmoud M. M.; Mohd Saudi, Madihah; Moha Alwi, Najwa Hayaati (Asian Research Publishing Network (ARPN), 2014)
Given an apparent lack of coherence and a paucity of computer system field of studies, research imitates and demonstrates non consensus in how computer security fits into the satisfaction, success, usage, efficiency, and effectiveness of computer system field. This study is a part of research aims to extend the Technology to Performance Chain model by including and examining the Computer Security Self-Efficacy construct, as recommend by several computer system field researchers. This paper used the statistical technique structural equation modeling and the partial least squares regression for estimating causal relations between computer security self-efficacy and internet banking usage. Outcomes confirm that confidentiality and availability effects computer security self-efficacy while in turn computer security self-efficacy impacts on usage. Computer security self-efficacy also partially mediates the impact of confidentiality, integrity, and availability on usage